2022
DOI: 10.3390/f13050658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Controlled Mycorrhization and Deficit Irrigation in the Nursery on Post-Transplant Growth and Physiology of Acer campestre L. and Tilia cordata Mill.

Abstract: The goal of this work was to assess the effects of mycorrhizal inoculation and deficit irrigation applied in the nursery on the post-transplant growth and physiology of Acer campestre L. and Tilia cordata Mill. For this purpose, 144 preconditioned plants were planted in an experimental plot in northern Italy and were monitored for three growing seasons. Controlled inoculation in the nursery enhanced the root colonization rate three years after transplanting only in Acer campestre. Inoculated Acer campestre sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…While its photoprotective system acclimated to drought, the acclimation did not last as long as in other species. This finding matches the finding comparing acclimation to drought between field maple and small-leaved lime [53]. The study found that field maple trees that experienced drought grew better in subsequent droughts than controls, while the drought acclimation did not help the lime trees.…”
Section: Discussionsupporting
confidence: 88%
“…While its photoprotective system acclimated to drought, the acclimation did not last as long as in other species. This finding matches the finding comparing acclimation to drought between field maple and small-leaved lime [53]. The study found that field maple trees that experienced drought grew better in subsequent droughts than controls, while the drought acclimation did not help the lime trees.…”
Section: Discussionsupporting
confidence: 88%
“…Mycorrhization and hardening in the nursery may be mandatory to achieve high survival rate (Corsini et al, 2022). However, the mycorrhiza is in large parts species specific and respective research and cultures are needed.…”
Section: Discussionmentioning
confidence: 99%